Influence of ultrasound on selected microorganisms, chemical and structural changes in fresh tomato juice - Agnieszka Starek (Nature Portfolio, 2021)
Abstract The paper presents the possibility of applying ultrasonic technology for inactivation of mesophilic aerobic microorganisms, lactic acid bacteria, coliform bacteria, and yeast with the maintenance of the chemical and structural properties of tomato juice. The research was conducted on fresh tomato juice obtained from the Apis F1 variety. Pressed juice was exposed to high power ultrasound and frequency 20 kHz with three operational parameters: ultrasound intensity (28 and 40 W cm−2), treatment time (2, 5, and 10 min), and product storage time (1, 4, 7 and 10 days). The temperature of the juice during the sonication ranged from 37 to 52 °C depending on the intensity of ultrasound and time of treatment. Effectiveness of the tested microorganisms eradication in the juice depended on the amplitude and duration of the ultrasound treatment. It was shown that the juice exposed to an ultrasonic field with an intensity of 40 W cm−2 for 10 min was microbiologically pure and free from spoilage microorganism even after 10 storage days. No statistically significant differences in pH were found between the untreated juice and the sonicated samples. The ultrasonic treatment was found to change the content of lycopene in small degree (both an increase and a decrease, depending on the processing time) and to induce a small decrease in the vitamin C content. The study suggests that the ultrasonic treatment can be successfully implemented on an industrial scale for the production of not-from-concentrate (NFC) tomato juice.